Ensiling hybrid Pennisetum with lactic acid bacteria or organic acids improved the fermentation quality and bacterial community - Feng, Qixian; Zhang, Juan; Ling, Wenqing; Degen, Abraham Allan; Zhou, Yi; Ge, Chenyan; Yang, Fulin; Zhou, Jing (Frontiers in Microbiology, 2023)
The aim of this study was to compare the effect of different additives on nutritional quality, fermentation variables and microbial diversity of hybrid Pennisetum silages. A control (CK – no additives) and seven treatments were tested, namely, Lactiplantibacillus plantarum (LP), Lentilactobacillus buchneri (LB), propionic acid (PA), calcium propionate (CAP), LP+LB; LP+PA and LP+CAP. In comparison with CK, all treatments increased the contents of crude protein and lactic acid, decreased the content of butyric acid, and altered the bacterial communities of the silage. Except for the CAP and LP+CAP treatments, the additives decreased pH and the ammonia nitrogen:total nitrogen (NH3-N:TN) ratio. The results of principal component analysis revealed that the PA, LP+PA and LP+LB treatments ranked as the top three silages. The PA and LP+PA treatments exhibited higher water-soluble carbohydrate content, but lower pH, and NH3-N:TN ratio than the other treatments. With the PA and LP+PA treatments, the relative abundances of Lactobacillus and Enterobacter decreased, and of Proteobacteria and Delftia increased, while the carbohydrate metabolism of the microorganisms improved. The LP and LB treatments reduced the Shannon and Simpson diversities. In the beta diversity, PA and LP+PA separated from the other treatments, indicating that there were differences in the composition of bacterial species. The relative abundance of Lactobacillus increased in the LP and LB treatments and of Leucanostoc and Weissella increased in the CAP and LP+CAP treatments. In summary, the addition of L. plantarum, L. buchneri, propionic acid, calcium propionate, and their combinations improved fermentation quality, inhibited harmful bacteria and conserved the nutrients of hybrid Pennisetum.